2022
DOI: 10.1080/2162402x.2022.2146860
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts and macrophages cooperate to create a pro-tumorigenic and immune resistant environment via activation of TGF-β/IL-6 pathway in neuroblastoma

Abstract: Tumor-associated macrophages (TAM) and cancer-associated fibroblasts (CAF) and their precursor mesenchymal stromal cells (MSC) are often detected together in tumors, but how they cooperate is not well understood. Here, we show that TAM and CAF are the most abundant nonmalignant cells and are present together in untreated human neuroblastoma (NB) tumors that are also poorly infiltrated with T and natural killer (NK) cells. We then show that MSC and CAF-MSC harvested from NB tumors protected human monocytes (MN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 68 publications
1
21
0
Order By: Relevance
“…Zhang et al revealed that CAFs interacted with monocytes via the IL-8/CCR2 pathway, thereby inducing M2-type macrophages, which protected cancer cells from NK cell-mediated killing by reducing the cytotoxicity of NK cells [ 102 ]. Analogous results were reported by Louault et al [ 103 ], in which they confirmed that the suppressive effect on NK cells from CAF-TAM collaboration relied on TGF-β1. TGF-β signalling is an important pathway involved in tumour immune evasion [ 104 , 105 ].…”
Section: Macrophage–tumour Stroma Interactions Facilitate Immunosuppr...supporting
confidence: 89%
“…Zhang et al revealed that CAFs interacted with monocytes via the IL-8/CCR2 pathway, thereby inducing M2-type macrophages, which protected cancer cells from NK cell-mediated killing by reducing the cytotoxicity of NK cells [ 102 ]. Analogous results were reported by Louault et al [ 103 ], in which they confirmed that the suppressive effect on NK cells from CAF-TAM collaboration relied on TGF-β1. TGF-β signalling is an important pathway involved in tumour immune evasion [ 104 , 105 ].…”
Section: Macrophage–tumour Stroma Interactions Facilitate Immunosuppr...supporting
confidence: 89%
“…In particular, we find occasionally that collagen accumulation is significantly reduced in the tumor tissues of collaborative therapy group (Figure g). It is widely recognized that extracellular matrix components in tumor tissues are mainly produced by cancer-associated fibroblasts (CAFs), which play crucial regulatory roles in the TME and are closely related to tumor progression and resistance to chemotherapy. , Concernedly, CAFs feature semblable characteristics with mesenchymal stromal cells (MSCs) in high-risk NB patients, and their presence typically indicates an unfavorable clinical prognosis. MSCs preconditioned with conditional medium from NB cells exhibit heightened sensitivity to ferroptosis inducers due to the downregulation of the system X C – /GSH/GPX4 pathway . Therefore, the lethality of this strategy against CAFs was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…In neuroblastoma, TAMs collaborate with cancer-associated fibroblasts (CAFs) and mesenchymal stromal cells (MSC) to support tumor progression, especially in relapse patients. TAMs induce CAF proliferation [ 73 ], and MSCs/CAFs shield monocytes from apoptosis through in an IL-6-dependent manner [ 95 ]. The interactions of monocytes and MSC resulted in the significant upregulation of several pro-tumorigenic cytokines and chemokines, including TGF-β1, MCP-1, IL-6, IL-8, and IL-4.…”
Section: Myeloid Subpopulations In the Neuroblastoma Microenvironmentmentioning
confidence: 99%